Arteriogenesis in murine adipose tissue is contingent on CD68+/CD206+ macrophages. (May 2017) - Seaman, Scott A.; Cao, Yiqi; Campbell, Chris A.; Peirce, Shayn M.
ABSTRACT: Objective: The surgical transfer of skin, fat, and/or muscle from a donor site to a recipient site within the same patient is a widely performed procedure in reconstructive surgeries. A surgical pretreatment strategy that is intended to increase perfusion in the flap, termed "flap delay, " is a commonly employed technique by plastic surgeons prior to flap transplantation. Here, we explored whether CD68 + /CD206 + macrophages are required for arteriogenesis within the flap by performing gain‐of‐function and loss‐of‐function studies in a previously published flap delay murine model. Methods and Results: Local injection of M2‐polarized macrophages into the flap resulted in an increase in collateral vessel diameter. Application of a thin biomaterial film loaded with a pharmacological agent (FTY720), which has been previously shown to recruit CD68 + /CD206 + macrophages to remodeling tissue, increased CD68 + /CD206 + cell recruitment and collateral vessel enlargement. Conversely, when local macrophage populations were depleted within the inguinal fat pad via clodronate liposome delivery, we observed fewer CD68 + cells accompanied by diminished collateral vessel enlargement. Conclusions: Our study underscores the importance of macrophages during microvascular adaptations that are induced by flap delay. These studies suggest a mechanism for a translatable therapeutic target that may be used to enhance the clinical flap delay procedure.